Legislative Theatre: A review of the laws of concilman Augusto Boal's political-theatre mandate (Olhares, 2024)
The experience of the political-theatrical mandate of councilor Augusto Boal (1993-1996) was fundamental for the development of the Legislative Theatre, which is a theatrical technique for drafting laws, legal measures and direct actions. This article intends to review the laws approved from Boal's political-theatrical mandate, either as author, co-author or by the Commission for the Defense of Human Rights (CDDH). For that, the deductive method is used, following the methodologies of bibliographical reading and exploratory research consulting three sources of information, namely; the first printing of the book Teatro Legislativo - versão beta (1996); the first edition of the book Teatro Legislativo (2020), edited by Fabiana Comparato and Julián Boal; and the Rio de Janeiro City Council website (www.camara.rio). There are three ways of counting laws arising from the mandate, the first considering those approved during the legislature; the second, considering those approved during and after the mandate, excluding the internal norms of the City Council; and the most comprehensive, which considers all those that had Boal's participation, including those approved after the end of his mandate. With the most comprehensive form, the present study responds to the divergences and points out the exact number of bills presented and laws approved that had the participation of the political-theatrical mandate.
Keywords: Augusto Boal; Legislative Theatre; Theatre of the Oppressed